2008
DOI: 10.1093/jaoac/91.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aflatoxins B1, B2, G1, and G2 and Ochratoxin A in Ginseng and Ginger by Multitoxin Immunoaffinity Column Cleanup and Liquid Chromatographic Quantitation: Collaborative Study

Abstract: The accuracy, repeatability, and reproducibility characteristics of a method using multitoxin immunoaffinity column cleanup with liquid chromatography (LC) for determination of aflatoxins (AF; sum of aflatoxins B1, B2, G1, and G2) and ochratoxin A (OTA) in powdered ginseng and ginger have been established in a collaborative study involving 13 laboratories from 7 countries. Blind duplicate samples of blank, spiked (AF and OTA added) at levels ranging from 0.25 to 16.0 g/kg for AF and 0.25 to 8.0 g/kg for OTA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 2 publications
0
31
0
Order By: Relevance
“…The fraction or percentage of the analyte that is recovered when the test sample is analyzed using the entire method is referred to as the method recovery [27]. Table 1 shows the percentage of AF recovery at a low, three-point intermediate, and high concentration levels spiked in three culture conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction or percentage of the analyte that is recovered when the test sample is analyzed using the entire method is referred to as the method recovery [27]. Table 1 shows the percentage of AF recovery at a low, three-point intermediate, and high concentration levels spiked in three culture conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent developments in animal nutrition like the use of protected concentrated proteins designed to bypass the rumen have to be taken into account in carry-over research. Recently, first steps were taken to develop commercial tests for multi-analysis [35,85,86].…”
Section: New Trends In Carry-over Researchmentioning
confidence: 99%
“…These mycotoxins pose a serious threat to human health through ingestion because of their carcinogenicity, mutagenicity, teratogenicity, and immunosuppression. A few publications have reported that aflatoxins (AFs) and ochratoxin A (OTA) have been found in ginger and its products with various contamination levels .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, in order to get high sensitivity, various techniques have been used in the purification of mycotoxins such as SPE , solid‐phase microextraction , and liquid–liquid extraction . Among them, immunoaffinity column (IAC) based SPE is the most widely used technique in the pretreatment of mycotoxins for its high specificity and selectivity toward selected mycotoxins in many complex matrices . Some publications have reported the determination of AFs or OTA in ginger or its products with two different separation conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation